Pre-Soaking cum Boiling Effects on Oxalate Content and Acridity of Elephant Foot Yam Corm - Kumar, Anuj; Ramakumar, Pola; Patel, Ashok; Gupta, Vijay Kumar; Singh, Ashish Kumar (JOURNAL OF ROOT CROPS, 2018)
Elephant foot yam (Amorphophallus paeoniifolius (Dennst.) Nicolson; EFY) has not been fully exploited due to the presence of oxalates which are anti-nutritional and responsible for causing acridity (itchingcum-burning) sensation in soft tissues. To realize the full benefits of EFY, it is necessary to explore the reduction in oxalate content. Soaking in alkali (A) (0.01, 0.05, 0.10%), saline (S) (2, 6, 10%) and acidulated-saline (P) (pH 3.5) followed by boiling for 30 min did not significantly reduce oxalate content. Oxalate content were 91.87-94.61, 94.60-98.58, 94.61-96.43 mg 100g-1 and tactile acridity score were 0.45-1.03, 1.05-1.68, 1.05-1.45 for A, S and P treatments, respectively. Alkaline presoaking caused reduction in the acridity sensation, while soaking in salt solution enhanced the acridity. Alkaline soaking treatment caused significant darkening of elephant foot yam. Cooking rather than salt treatments reduced oxalate significantly, presumably due to leaching and hydrothermal degradation of oxalates. Proper cooking of EFY is desirable to reduce oxalates before consumption.